2021
DOI: 10.54530/jcmc.485
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Teenage Pregnancy Among Dalit Ethnic Groups in Bharatpur Metropolitian City, Chitwan

Abstract: Background: Teenage pregnancy refers to any pregnancy from a girl who is 10-19 years of age. This study aimed at accessing the factors influencing teenage pregnancy at first birth among the Dalit ethnic groups in Bharatpur Metropolitan City. Methods: A community based cross-sectional study using face-to-face interview method was carried out in Bharatpur Metropolitan City, Chitwan, Nepal. A total of 217 married Dalit women who had given birth to at least one child and who were less than 25 years of age during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…A descriptive research study among Chepang women in Korak Village Development Committee, Chitwan District showed that 58.1% of the participants had their first childbirth aged 17-19 years [ 8 ]. Another study conducted among 217 married women of Dalit groups showed that 42.9% of them had given birth to their first child during their teenage years, which suggested that the rate of adolescent pregnancy may be higher among specific ethnicities [ 9 ]. This is supported by the findings of a 12-month observational study in 12 hospitals in Nepal, which showed that women from disadvantaged ethnic groups have a higher likelihood of being adolescent mothers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A descriptive research study among Chepang women in Korak Village Development Committee, Chitwan District showed that 58.1% of the participants had their first childbirth aged 17-19 years [ 8 ]. Another study conducted among 217 married women of Dalit groups showed that 42.9% of them had given birth to their first child during their teenage years, which suggested that the rate of adolescent pregnancy may be higher among specific ethnicities [ 9 ]. This is supported by the findings of a 12-month observational study in 12 hospitals in Nepal, which showed that women from disadvantaged ethnic groups have a higher likelihood of being adolescent mothers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with adolescent pregnancy include low socioeconomic status (SES), unemployment, a low educational level, a lack of access to media exposure regarding public health issues, unplanned pregnancy, early marriage, sexual risk behaviors, family experience of adolescent birth, peer pressure, and a lack of sex education and healthcare service [ 7 - 9 ]. In Nepal, marrying at an early age is linked with a higher likelihood of adolescent pregnancy, with more than one-third of women who marry before their 15th birthday having 3 or more children.…”
Section: Introductionmentioning
confidence: 99%